Studies on transgenic tobacco plants containing geminiviral DNA - Babaya, Michelle (Faculty of Science, 2026)
The ability to transform plant genomes with foreign genetic material by means of the Agrobacterium tumefaciens Ti plasmid system has made it possible to test whether plant resistance to viruses can be increased by incorporating viral nucleotide sequences into the nuclear genome of the host. As part of a model system designed to explore the feasibility of making cereals resistant to maize streak virus (MSV), tobacco plants were to be transformed with one or more genome-equivalents (multimers) of Port Elizabeth (PE) and Nigerian (N) isolates of (MSV), and analysed for evidence of expression of the viral coat protein. The constructs were mobilized into A. tumefaciens [C58C1Rif (pGV2260)] and introduced into tobacco by co-cultivation with leaf discs. Putatively transgenic kanamycin-resistant calli were tested for the presence of the plasmid vector marker enzyme, neomycin phosphotransferase (NPT-II). Southern hybridization analysis was used to establish the integration of MSV DNA into tobacco. Expression of the MSV coat protein was tested for by Western blotting and enzyme-linked immunosorbent . assay ( ELISA) techniques. Transformed calli all expressed NPT-II activity and contained integrated MSV DNA, but no coat protein could be detected serologically. A minor part of the project involved the study of a new strain of MSV isolated from the Koedoeskop area in South Africa which produced severe disease symptoms in maize. The genomic DNA was purified, the genome cloned into pUC19 and mapped. The restriction enzyme cleavage map of the new isolate, MSV-KoeI, was compared to. those of 8 other MSV isolates. Similarities and differences between these maps are discussed.